The social order of the bazaar: Socio-economic embedding of retail and trade in Kunduz and Imam Sahib - Nasratullah Yarash; Katja Mielke (University of Bonn, Center for Development Research (ZEF), 2011)
Afghanistan's economy is undergoing change with recently surging GDP-growth. This empirical paper looks at two urban markets to investigate how the positive economic performance is based on local retail and trade in Kunduz and Imam Sahib. Against the backdrop of an historical overview, the main features of local production, marketing and sales are linked with an analysis of the institutional and social embeddedness of shopkeepers and craftsmen. The findings show a close interdependence of the bazaar with its rural hinterland, as the district population constitutes the main purchasers of goods and suppliers of agricultural produce. Both bazaars are linked with regional and world markets. As centres of economic activity in Kunduz province, the markets provide the main revenue source for the respective municipal administration. Contrary to the national trend expressed in GDP-growth, it is shown that, at the local level, profits, employment, livelihood-making and public works are an outcome of constant negotiation and the ever-present competition of multiple ordering ideas, institutions and values ingrained in the different stakeholders present.
Keywords: 330; bazaar; retail; trade; local governance; Afghanistan; Kunduz Province